2013
DOI: 10.1097/aln.0b013e3182a8a8e7
|View full text |Cite
|
Sign up to set email alerts
|

Using Exome Data to Identify Malignant Hyperthermia Susceptibility Mutations

Abstract: Background Malignant hyperthermia susceptibility (MHS) is a life-threatening, inherited disorder of muscle calcium metabolism, triggered by anesthetics and depolarizing muscle relaxants. An unselected cohort was screened for MHS mutations using exome sequencing. Our aim was to pilot a strategy for the RYR1 and CACNA1S genes. Methods Exome sequencing was performed on 870 volunteers not ascertained for MHS. Variants in RYR1 and CACNA1S were annotated using an algorithm that filtered results based on mutation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 31 publications
0
74
0
Order By: Relevance
“…Initial efforts using whole exome sequencing have largely resulted in validation of RYR1 mutations as the primary cause of disease in the majority of cases [11,16]. These studies have also revealed many RYR1 variants of unknown significance that require further validation in order to be listed as pathogenic.…”
Section: How Is the Disorder Treated?mentioning
confidence: 99%
See 2 more Smart Citations
“…Initial efforts using whole exome sequencing have largely resulted in validation of RYR1 mutations as the primary cause of disease in the majority of cases [11,16]. These studies have also revealed many RYR1 variants of unknown significance that require further validation in order to be listed as pathogenic.…”
Section: How Is the Disorder Treated?mentioning
confidence: 99%
“…It is now clear that RYR1-related myopathies are the most common nondystrophic muscle conditions of childhood and that the clinical spectrum for the disorders is vast [36,37]. One important issue to emerge is how to interpret identified sequence variants in RYR1 that are of uncertain pathogenicity [11,16]. AS RYR1 mutations are associated with such a broad range of disease, most novel variants identified in RYR1 have the potential of causing disease.…”
Section: What Are Key Current Issues Related To the Disease?mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this point, exome sequencing performed on 870 volunteers without medical or family histories for MHS identified three RYR1 variants predicted to predispose to MH reactions. [39] Finally, the case reported by Potts et al illustrate the continuous use of dantrolene for treatment of cramps and prevention of RM: these 30-year-old identical twin brothers with persistent hyperCKemia, severe debilitating muscle cramps, and unexplained RM both required oral dantrolene therapy to control their symptoms [34].…”
Section: Malignant Hyperthermia (Mh)mentioning
confidence: 99%
“…24 The prevalence of genetic variants associated with MH susceptibility was estimated at 1 in 3000. 1,25 To date, 34 RYR1 variants and 2 CACNA1S variants have been confirmed as causing MH and recommended for diagnostic genetic testing by the European Malignant Hyperthermia Group. 14 4.…”
Section: Definition Of Malignant Hyperthermiamentioning
confidence: 99%